Analysis of the Management of zakat and asn infaq in the City of Cilegon Banten - Widiyatmoko, Bambang; Bahri, Syaeful; Syarifuddin, Efi (Institute of Computer Science (IOCS), 2024)
One of the pillars of Islamic philanthropy is Zakat. Undoubtedly, it must be done correctly and comply with applicable sharia. The aim of this research is to describe how Zakat and Infaq are managed for ASN Cilegon City and how effective and efficient Zakat management is in Baznas Cilegon City Banten. The approach taken in this research uses a qualitative approach with the literature study method (case study). Data sources in research collect two sources, namely primary and secondary. Primary informants directly include (the community, ASN and Cilegon City Baznas administrators). Secondary, namely strengthening data from primary such as: Journal articles, E-Books, Online Proceedings, magazines, newspapers and other internet media. Meanwhile, data collection techniques include observation interviews, documentation and triangulation. The analysis technique used in this research is using Miles and Huberman's theory of data reduction, data display, data verification and drawing conclusions. So, this research resulted in optimizing the distribution of Baznas, the efficiency of distributing Zakat funds, the percentage of distribution efficiency levels, the percentage of Cilegon City Zakat management. So, it can be concluded that Cilegon City Baznas maximizes existing human resources (HR) both internally and externally to Baznas itself. Research findings show that optimization can be said to be quite optimal. For 2018–2022, the average distribution efficiency of zakat funds is 95.8%.